Communist parties revisited : sociocultural approaches to party rule in the Soviet bloc, 1956-1991 - Bergien, Rüdiger; Gieseke, Jens (New York : Berghahn Books, 2018)
"The ruling communist parties of the postwar Soviet Bloc possessed nearly unprecedented power to shape every level of society; perhaps in part because of this, they have been routinely depicted as monolithic, austere, and even opaque institutions. Communist Parties Revisited takes a markedly different approach, investigating everyday life within basic organizations to illuminate the inner workings of Eastern Bloc parties. Ranging across national and transnational contexts, the contributions assembled here reconstruct the rituals of party meetings, functionaries' informal practices, intra-party power struggles, and the social production of ideology to give a detailed account of state socialist policymaking on a micro-historical scale"--
Communist parties revisited: cultural approaches to party rule in the Soviet Bloc, 1956-1991 / Rüdiger Bergien and Jens Gieseke -- The paradox of party discipline in the Khrushchev-era Communist Party / Edward Cohn -- "It Is not possible to allow past mistakes to come again": recruitment policy in the CPCS in the 1970s and 1980s / Michel Christian -- Behind closed doors: the erosion of SED party life in the 1980s / Sabine Pannen -- The successive dissolution of the "uncivil society": tracking SED party members in opinion polls and secret police reports, 1969-1989 / Jens Gieseke -- On the way to party pluralism?: the PZPR and the reform of the socialist party system in 1988-1989 / Frédéric Zalewski -- Communist Party apparatuses as steering organizations: paths of development in East Central Europe / Christoph Boyer -- The Central Committee Department of Party Organs under Khrushchev / Alexander Titov -- True believers becoming funded experts?: personnel profile and political power in the SED Central Committee's Sectoral Apparatus, 1946-89 / Rüdiger Bergien -- Paternalism in local practice: the logic of repression, ideological hegemony and the everyday management of society in an SED local secretariat / Andrea Bahr -- The SED Bezirk secretaries as brokers of territorial interests in the GDR / Jay Rowell -- The idea of social unity and its influence on the mechanisms of a totalitarian regime in the years 1956-1980 / Krzysztof Dąbek -- Foreign policymaking and party-state relations in the Soviet Union during the Brezhnev era / Mark Kramer -- Erich Honecker, the "leading representative": a generational perspective / Martin Sabrow -- Inside the system: the CPSU Central Committee, Mikhail Gorbachev's Komanda, and the end of Communist rule in Russia / Jan C. Behrends -- The ironies of membership: the ruling Communist Party in comparative perspective / Padraic Kenney.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 04, 2022).
eBooks on EBSCOhost
Keywords: Communist parties -- Europe, Eastern -- History -- 20th century; Communist parties -- Communist countries -- History; Communism -- Soviet Union -- History -- 20th century; Europe, Eastern -- Social conditions -- 20th century; Europe, Eastern -- Politics and government -- 20th century; Communist countries -- Social conditions -- 20th century; Communist countries -- Politics and government -- 20th century; Partis communistes -- Europe de l'Est -- Histoire -- 20e siècle.; Partis communistes -- Pays socialistes -- Histoire; Communisme -- URSS -- Histoire -- 20e siècle.; Europe de l'Est -- Conditions sociales -- 20e siècle.; Europe de l'Est -- Politique et gouvernement -- 20e siècle.; Pays socialistes -- Conditions sociales -- 20e siècle.; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism; HISTORY / Europe / Russia & the Former Soviet Union; Social conditions; Politics and government; Communist parties; Communism; Eastern Europe; Communist countries; Soviet Union; 1900-1999; History